Zeolite-A Synthesis from Glass - Saraswati, Indah (JURNAL SAINS DAN MATEMATIKA, 2015)
Zeolite can be used as ion exchanger, catalyst, and adsorbent. Â One type of synthetic zeolites is zeolite-A which being developed to overcome the weakness of natural zeolites for their difference of pore size. This research is aimed to study the synthesized of zeolite-A from wasted glasses as silica source. Hydrogel method was used by reacting sodium aluminate into a sodium silicate solution. The gel formed was heated at 80Â°C for 8 hours and to produce a white solid. The solid result were characterized by XRD, FTIR, and AAS. The XRD analysis shown that the yield which formed closest to zeolite-A structure was in concentrate variation of sodium silicate and sodium aluminate of 1.05 : 1. This result also can be confirmed by FTIR analysis.